Bat Caliciviruses and Human Noroviruses Are Antigenically Similar and Have Overlapping Histo-Blood Group Antigen Binding Profiles - Jacob F. Kocher (American Society for Microbiology, 2018)
ABSTRACT Emerging zoonotic viral diseases remain a challenge to global public health. Recent surveillance studies have implicated bats as potential reservoirs for a number of viral pathogens, including coronaviruses and Ebola viruses. Caliciviridae represent a major viral family contributing to emerging diseases in both human and animal populations and have been recently identified in bats. In this study, we blended metagenomics, phylogenetics, homology modeling, and in vitro assays to characterize two novel bat calicivirus (BtCalV) capsid sequences, corresponding to strain BtCalV/A10/USA/2009, identified in Perimyotis subflavus near Little Orleans, MD, and bat norovirus. We observed that bat norovirus formed virus-like particles and had epitopes and receptor-binding patterns similar to those of human noroviruses. To determine whether these observations stretch across multiple bat caliciviruses, we characterized a novel bat calicivirus, BtCalV/A10/USA/2009. Phylogenetic analysis revealed that BtCalV/A10/USA/2009 likely represents a novel Caliciviridae genus and is most closely related to "recoviruses." Homology modeling revealed that the capsid sequences of BtCalV/A10/USA/2009 and bat norovirus resembled human norovirus capsid sequences and retained host ligand binding within the receptor-binding domains similar to that seen with human noroviruses. Both caliciviruses bound histo-blood group antigens in patterns that overlapped those seen with human and animal noroviruses. Taken together, our results indicate the potential for bat caliciviruses to bind histo-blood group antigens and overcome a significant barrier to cross-species transmission. Additionally, we have shown that bat norovirus maintains antigenic epitopes similar to those seen with human noroviruses, providing further evidence of evolutionary descent. Our results reiterate the importance of surveillance of wild-animal populations, especially of bats, for novel viral pathogens. IMPORTANCE Caliciviruses are rapidly evolving viruses that cause pandemic outbreaks associated with significant morbidity and mortality globally. The animal reservoirs for human caliciviruses are unknown; bats represent critical reservoir species for several emerging and zoonotic diseases. Recent reports have identified several bat caliciviruses but have not characterized biological functions associated with disease risk, including their potential emergence in other mammalian populations. In this report, we identified a novel bat calicivirus that is most closely related to nonhuman primate caliciviruses. Using this new bat calicivirus and a second norovirus-like bat calicivirus capsid gene sequence, we generated virus-like particles that have host carbohydrate ligand binding patterns similar to those of human and animal noroviruses and that share antigens with human noroviruses. The similarities to human noroviruses with respect to binding patterns and antigenic epitopes illustrate the potential for bat caliciviruses to emerge in other species and the importance of pathogen surveillance in wild-animal populations.